Responding to the challenges of impact assessment of participatory research and gender analysis - Lilja, Nina; Dixon, John A. (Cambridge University Press, 2008)
Since the Green Revolution, the public-sector's agricultural research strategy for increasing food crop productivity has been explicitly based on the premise that technology can cross political and agro-climatic boundaries, primarily through the training and visit system of extension (also known as transfer of technology and the pipeline model). Today, a different strategy is emerging. Efforts to develop the necessary institutional capacity for more client-oriented participatory research, particularly in plant breeding, are now a central part of the public-sector agricultural research strategy. Greater use of participatory and gender-analysis approaches in agricultural research has significant conceptual and methodological implications for impact assessment and institutional learning.